Forensic aspects of dissociative identity disorder - Sachs, Adah; Galton, Graeme (Forensic psychotherapy monograph series., 2008)
This ground-breaking book examines the role of crime in the lives of people with Dissociative Identity Disorder, formerly known as Multiple Personality Disorder, a condition which appears to be caused by prolonged trauma in infancy and childhood. This trauma may be linked with crimes committed against them, crimes they have witnessed, and crimes they have committed under duress. This collection of essays by a range of distinguished international contributors explores the complex legal, ethical, moral, and clinical questions which face psychotherapists and other professionals working with peopl.